Activated-carbon/TiO2 composites preparation: An original grafting by milling approach for solar water treatment applications. Issue 5 (October 2020) - Ribeiro, E.; Plantard, G.; Teyssandier, F.; Maury, F.; Sadiki, N.; Chaumont, D.; Goetz, V.
Graphical abstract: Highlights: AC/TiO2 Composites have been synthesized by a new approach. Synthesis parameters study led to a control of the composite powder particles size, distribution and homogeneity. Adsorbent and photocatalytic properties have been quantified showing multifunctional behavior of AC/TiO2 . Abstract: The aim of this work was to highlight feasibility of a new approach to synthesize Activated-Carbon (AC)/TiO2 composite materials. The main interest of these materials is for pollutants removal applications thanks to their multi-functionality. AC/TiO2 composites were prepared by one-step mechanosynthesis route. Morphological and structural properties were investigated through SEM, EDS, XRD, and BET techniques. It was found that the preparation process leads to the formation of an aggregate shape homogenously composed AC/TiO2 powder with a narrow particles size distribution, which mean diameter was 3.75 μm. Initial component structural properties were found to be strongly affected by the process, resulting in significant changes of TiO2 crystallinity and AC microtexture. The introduction of 5 min pauses during the process was enough to totally preserve TiO2 phases, crystallinity, and AC microporous network. Composites multi-functional properties were investigated using batch adsorption and photodegradation experiments. Adsorption studies revealed that AC/TiO2 aggregates exhibit good adsorption capacity with caffeine and a maximum adsorbed amount of 353 mg.g −1 . Photocatalytic experiments highlighted that AC/TiO2 presents a photo-oxidation ability. Photodegradation apparent kinetic rate fitted with a first-order law gave a value of 1.04 × 10 -5 s -1 for the composite and ten times higher for pure TiO2 . These results allowed to conclude that mechanosynthesis is an effective route to produce bi-functional AC/TiO2 composites with efficient adsorption capacity for water treatment applications. It also suggests the need of further radiative transfer studies to understand light scattering and absorption inside these materials, which could lead to some improvement of these promising materials.